Secondary metabolites, hormonal homeostasis, and antioxidant enzymes of Moringa oleifera in response to white or violet Light Emitting Diodes (LEDs) combined with cytokinins under tissue culture conditions - Lina M. ABU-ZIADA; Samia A. HAROUN; Rasha M.E. GAMEL; Mohamed A. ABBAS; Mahmoud R. SOFY; Heba Y. EL-BANNA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2022)
The present study was carried out between 2021 and 2022 at the tissue culture lab and experimental station of the vegetable and floriculture department, faculty of agriculture, Mansoura University. Using mature seeds, Moringa oleifera is propagated on a large scale and in rapid succession by in vitro culture. Two types of cytokinin: 6-benzylaminopurin (BAP), and thidiauron (TDZ) singly at three different concentrations (0, 1, or 2 mg/L), were used, as well as light-emitting diode systems (LEDs) (white as control and violet; the combination of red and blue; 1:1). After incubation for 30 days, the obtained results showed that the survival percentage increased by the treatments with the maximum value (85%) by MS medium supplemented with 2 mg/L TDZ, under violet LEDs illumination. However, the addition of thidiazuron (TDZ) to the medium did not propagate shoot, and this treatment recorded 100% callus formation other than BAP. The maximum number of axillary shoots per explant and the number of leaves recorded in the MS medium contained 2 mg/L BAP under violet LEDs. Compared to the control values, all the used treatments generally caused surprisingly stimulating the determined antioxidant enzymes and compounds (peroxidase, polyphenol oxidase &catalase and phenols, flavonoids, anthocyanin& ascorbic acid). Concerning the phytohormone content of the hormone-free medium (control), IAA, kinetin, and zeatin increased. Meanwhile, GA3 and ABA decreased with the used treatments.